Unter Gleichen APARIUZ XXII - Altobelli, Ada Sofie (Apariuz, 2021)
This year's XXII edition of the APARIUZ series, entitled "Unter Gleichen" ("Among Equals"), programmatically takes up the fiftieth anniversary, scheduled for 2021, of one of the most significant legal-historical and political events in Switzerland: the introduction of universal women's suffrage and voting rights. Based on this milestone, which is hard to surpass in its social and legal implications, the thirteen contributions in this anthology, written by young female scholars from all legal disciplines, examine a wide variety of questions about the complex and multifaceted relationship between law, equality, and justice.